Answer:
42
Step-by-step explanation:
x/3+12 = 26
Multiply everything by 3 to eliminate the fraction
x+36=78
subtract 36 on both sides
x=42
42/3=14
14+12=26
To do a two-column proof, you must know the definitions of the terms that are being used. Also, you must know the postulates and theorems you have learned so far. You look at the given information, and using the definitions, postulates, and theorems, you reason in your mind how to go from the given to the conclusion, step by step. You write each step and the accompanying reason that allows you to conclude each step.
Y - 3 = X + 2 ...............….... (1)
2X - 1 = Y ........................... (2)
From (2),
2X - 1 = Y
Y = 2X - 1
Sub (2) into (1),
(2X-1) - 3 = X + 2
2X - 1 - 3 = X + 2
2X - X = 2 + 1 + 3
X = 6
Sub x=6 into (1),
Y = 2(6) - 1
Y = 12 - 1
Y = 11